Ghosts in John Banville’s The Sea - Pierre Vitoux (Études Britanniques Contemporaines, 2008)
When the narrator of The Sea returns after fifty years to the place by the sea where his years of childhood had come to a tragic end, he notes that his sense of the uncanny is unorthodox, since its origin is not, or not chiefly, the presence around him of the ghosts from the past, but the aura surrounding the new world he had discovered in his innocence. But the reader finds itertextual clues in the text to solve the apparent paradox. They refer him to Freud’s description of the unending struggle of the ego to maintain a coherent personality, and also to his early speculations in his essay ‘The ‘Uncanny’ ‘ about what he will call the death instinct. That instinct is intertextually related in the novel to the ‘high instincts’, the ‘intimations of immortality’ of Wordsworth’s Ode, but as their obverse, so that the myth of the birth out of the sea is here steeped in the mood of serene disenchantment characteristic of the ironic mode of post-Romantic fiction.